AL-AKHTHA’ FII IKTISAB AL-TSUNAIYAT AL-SHUGHRA - Huda, Miftahul (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
Language acquisition starts from the ability of listening basic letter(iktisab al-ashwat) since child age. The letter of a language is limited in number, and sometimes there is similarity of letters among languages. The similarity of letters in two languages make it easy to learn the language. On the contrary, the obstacle of language learning can be caused by different letters between two languages (mother tongue and second/foreign language). The problem may be caused by minimal pairs (tsunaiyat al-shughro). This research aims at finding out the error of minimal pair acquisition, with the subject of Indonesian students in Jami’ah Malik Saud Saudi Arabia, with the method of error analysis. The study concludes that in iktisab al-ashwat of minimal pairs, the error is around 3,3 %-58,3%. Second: the error on minimal pairs occurs on the letters shift ?? ?? ? to be ? , letter ? to be ? , letter ? to be ? , letter ? to be ? , letter ? to be ?? , and letter ? to be ?.